Izzy Paints - Miller, Tim (New York, New York: Balzer + Bray, an imprint of HarperCollinsPublishers, 2022)
After Izzy visits an art museum in the big city, he becomes inspired to make his own art.
new kids book 2025 spring.
Keywords: Koalas -- Juvenile fiction; Museums -- Juvenile Fiction; Art appreciation -- Juvenile fiction; Creative ability -- Juvenile Fiction; Picture books